2019
DOI: 10.1093/mnras/stz3236
|View full text |Cite
|
Sign up to set email alerts
|

The growth of brightest cluster galaxies and intracluster light over the past 10 billion years

Abstract: We constrain the evolution of the brightest cluster galaxy plus intracluster light (BCG+ICL) using an ensemble of 42 galaxy groups and clusters that span redshifts of z = 0.05 − 1.75 and masses of M 500,c = 2 × 10 13 − 10 15 M . Specifically, we measure the relationship between the BCG+ICL stellar mass M and M 500,c at projected radii 10 < r < 100 kpc for three different epochs. At intermediate redshift (z = 0.40), where we have the best data, we find M ∝M 500,c 0.48±0.06 . Fixing the exponent of this power la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 60 publications
8
45
0
Order By: Relevance
“…We also exclude all BCGs at redshift z > 0.9 on the blue histogram. studies found in the literature based on HST images, such as Bai et al (2014), DeMaio et al (2019. We studied the luminosity profiles of these galaxies and how they evolve as a function of redshift.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also exclude all BCGs at redshift z > 0.9 on the blue histogram. studies found in the literature based on HST images, such as Bai et al (2014), DeMaio et al (2019. We studied the luminosity profiles of these galaxies and how they evolve as a function of redshift.…”
Section: Discussionmentioning
confidence: 99%
“…4). Postman et al (2012a), Bai et al (2014), Donahue et al (2015), West et al (2017), DeMaio et al (2019, Durret et al (2019), andSazonova et al (2020). We also add five more distant clusters at z ≥ 0.8, as well as the cluster Abell 2813 at z = 0.29.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Additional evidence for such a connection between diffuse intracluster light and the underlying cluster dark matter distribution can be found in a few other observation-based studies. Many have noticed a correlation between cluster mass (including dark matter mass) and total diffuse light luminosity or stellar mass especially at large radius (e.g., Zibetti et al 2005;Kluge et al 2020;DeMaio et al 2020;Huang et al 2018b,a). Moreover, Zhang et al (2019b, hereafter Z19) discovered that the ratio between diffuse light surface brightness and a weak-lensing measurement-based cluster mass-density model appears to be flat with a cluster radius outside 100 kpc, and that diffuse intracluster light radial profiles are "self-similar", i.e., independent of cluster mass after scaling by cluster radius.…”
mentioning
confidence: 99%